The Improvement of Students’ Awarness and Motivation to Learn English Trough International Webinar: The Importance of English Competency in Building Intercultural Communication - Ade Tuti Turistiati; Dimas Reza Amrullah; Shafitri Shafitri (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2023)
English is an international language that is the primary choice for individuals in intercultural communication with people from various nations. However, intercultural communication with foreigners is often constrained by inadequate English skills. This condition occurs in students in the Communication Studies Study Program and Digital Business Study Program, Faculty of Business and Social Sciences, Universitas Amikom Purwokerto. The student's English proficiency is relatively low. Based on interviews with around 50 English Club participants at the Faculty of Business and Social Sciences, 75% of students have basic English skills and only 25% can be categorized as the intermediate level of English. To raise awareness and motivate students to learn English, we conducted a seminar “The Importance of English Competency in Building Intercultural Communication”. The seminar was facilitated by Universitas Amikom Purwokerto and Huachiew Chalermprakiet University, Thailand. It was a program of international community service and an implementaion of the MoU between Universitas Amikom Purwokerto and Huachiew Chalermprakiet University. From the evaluation after participating in this seminar, participants’s response are positive. The seminar is useful and inspiring for them.  More than 50% of participants plan to learn English individually through online and offline courses, both formal and informal. It was also expected that in the future the kind of seminar can be held directly (off line).